Personalizing voriconazole dosing in Chinese hematological patients: CYP2C19 phenotype and albumin-bilirubin grade as key predictors of trough concentrations - Hu, Lin; Tang, Xi; Li, Yanfei; Huang, Juanjuan (Frontiers in Pharmacology, 2025)
PurposeThis retrospective, single-center study aimed to evaluate the genetic and non-genetic factors influencing voriconazole (VRC) trough concentration (Ctrough), efficacy and safety in hematological patients.MethodsMedical records of inpatients were reviewed retrospectively. Univariate and multivariate analyses were performed to identify factors contributing to the variability of VRC Ctrough.ResultsA total of 375 VRC Ctrough measurements from 89 patients were analyzed. At the time of the initial Ctrough assessment, 74 patients (83.1%) received oral VRC, while 15 patients (16.9%) received intravenous VRC. Among these first Ctrough measurements, 68.5% of patients achieved the target therapeutic range (1.0–5.5 mg/L), whereas 28.1% had subtherapeutic concentrations and 3.4% had supratherapeutic concentrations. The dose-normalized VRC Ctrough (Ctrough/D) were significantly higher in poor metabolizers (PMs) compared to normal metabolizers (NMs) (P = 0.001) and intermediate metabolizers (IMs) (P = 0.021). The albumin-bilirubin (ALBI) grade, a novel liver function assessment tool, was significantly associated with VRC Ctrough/D. Patients with ALBI grade 3 had significantly higher Ctrough/D values compared to those with grade 2 (P = 0.001) and grade 1 (P < 0.001). The linear mixed model revealed that sex, concomitant glucocorticoid use, creatinine clearance rate (Ccr), CYP2C19 genotype, and ALBI grade were statistically significant predictors of VRC Ctrough/D. A total of 10 patients (11.2%) had their VRC dosage adjusted based on therapeutic drug monitoring (TDM). The overall treatment success rate was 75.3% (67/89). Adverse drug reactions (ADRs) were observed in 12 patients (13.5%) during VRC therapy.ConclusionCYP2C19 phenotype, ALBI grade, sex, Ccr and concomitant use of glucocorticoids contribute to the variability of VRC Ctrough and should be comprehensively considered when determining VRC dosage in Chinese hematological patients.